Self-collected vaginal sampling for the detection of genital human papillomavirus (HPV) using careHPV among Ghanaian women - Dorcas Obiri-Yeboah; Yaw Adu-Sarkodie; Florencia Djigma; Anna Hayfron-Benjamin; Latif Abdul; Jacques Simpore; Philippe Mayaud (BMC, 2017)
Abstract Background Detection of genital HPV DNA is recommended as an important strategy for modern cervical cancer screening. Challenges include access to services, the reliance on cervical samples taken by clinicians, and patient's preference regarding provider gender. The objective of this research was to determine the acceptability, feasibility and performance of alternative self-collected vaginal samples for HPV detection among Ghanaian women. Methods A comparative frequency-matched study was conducted in a systematic (1:5) sample of women attending HIV and outpatient clinics in the Cape Coast Teaching Hospital, Ghana. Participants were instructed on self-collection (SC) of vaginal samples using the careHPV brush and a clinician-collected (CC) cervical sample was obtained using a similar brush. Paired specimens were tested for HPV DNA (14 high-risk types) by careHPV assay (Qiagen) and by HPV genotyping (Anyplex II, Seegene). Results Overall, 194 women of mean age 44.1 years (SD ± 11.3) were enrolled and 191 paired SC and CC results were analysed. The overall HPV detection concordance was 94.2% (95%CI: 89.9-97.1), Kappa value of 0.88 (p < 0.0001), showing excellent agreement. This agreement was similar between HIV positive (93.8%) and negative (94.7%) women. Sensitivity and specificity of SC compared to CC were 92.6% (95%CI: 85.3-97.0) and 95.9% (95%CI: 89.8-98.8) respectively. The highest sensitivity was among HIV positive women (95.7%, 95%CI: 88.0-99.1) and highest specificity among HIV negative women (98.6%, 95%CI: 92.4-100). Overall, 76.3% women found SC very easy/easy to obtain, 57.7% preferred SC to CC and 61.9% felt SC would increase their likelihood to access cervical cancer screening. Conclusions The feasibility, acceptability and performance of SC using careHPV support the use of this alternative form of HPV screening among Ghanaian women. This could be a potential new affordable strategy to improve uptake of the national cervical cancer screening program.